ECUIVALENCE PROBLEMS IN TRANSLATION (Лучшие интеллектуальные исследования, 2025)
Abstract: This article explores the multifaceted concept of equivalence in translation, particularly the challenges it poses when translating between English and Uzbek. It examines theoretical perspectives from Nida, Newmark, and Catford, and highlights specific problems in lexical, grammatical, and cultural equivalence. Case studies from legal, literary, and religious texts illustrate practical difficulties and solutions. The paper also discusses effective strategies to address these problems and offers pedagogical suggestions for teaching equivalence in translation studies. The goal is to demonstrate that achieving equivalence is not about literal accuracy alone but about functional and cultural resonance.